Efficacy of Standard and Accelerated (10 Minutes) Corneal Crosslinking in Keratoconus Stabilization - Stock RA (Dove Medical Press, 2020)
Ricardo Alexandre Stock, Gustavo Brustollin, Rafael André Mergener, Elcio Luiz Bonamigo Medical School of the University of the West of Santa Catarina (Universidade do Oeste de Santa Catarina – UNOESC), Joaçaba Campus, State of Santa Catarina, BrazilCorrespondence: Ricardo Alexandre Stock Email ricardostockreal@gmail.comPurpose: To evaluate whether Accelerated CXL for 10 minutes is as effective as standard CXL for 30 minutes for the treatment of progressive keratoconus.Patients and Methods: Eighty-two eyes of 62 patients with keratometry examinations performed before and 6 months after surgery were studied. A total of 39 eyes underwent standard CXL with UVA irradiation of 3 mW/cm2 for 30 minutes and 32 eyes underwent Accelerated CXL UVA irradiation of 9 mW/cm2 for 10 minutes. The eyes of all patients had corneal thicknesses of at least 450 microns (400 microns after epithelium removal).Results: The means of the keratometry measurements in the preoperative period for the eyes subjected to standard CXL were 46.27 dioptres (D) on the flat axis (K1) and 48.93 D on the steep axis (K2). Postoperatively, K1 was 46.21 D and K2 was 48.97 D, a difference without statistical significance (p = 0.47 and p = 0.48, respectively). In the Accelerated CXL protocol, the preoperative measurements were 44.55 D and 46.19 D for K1 and K2, respectively. In the postoperative period, K1 was 43.37 D, and K2 was 46.64 D (p = 0.38 and p = 0.27, respectively). In the standard group, the mean maximum keratometry (Kmax) preoperatively was 55.87 D, with no statistical significance (p = 0.29). In the preoperative period, the Kmax of the Accelerated group was 51.15 D, with no statistical significance (p = 0.32).Conclusion: Based on the keratometry results, the accelerated protocol was as effective as the standard protocol for keratoconus stabilization.Keywords: corneal diseases, cornea, keratometry, efficacy